Evaluation of near-threshold fatigue crack propagation in Ti-6Al-4V Alloy with harmonic structure created by Mechanical Milling and Spark Plasma Sintering (Fracture and Structural Integrity, 2015)
Titanium alloy (Ti-6Al-4V) having a bimodal “harmonic structure”, which consists of coarsegrainedstructure surrounded by a network structure of fine grains, was fabricated by mechanical milling (MM)and spark plasma sintering (SPS) to achieve high strength and good plasticity. The aim of this study is toinvestigate the near-threshold fatigue crack propagation in Ti-6Al-4V alloy with harmonic structure. Ti-6Al-4Valloy powders were mechanically milled in a planetary ball mill to create fine grains at powder’s surface and theMM-processed powders were consolidated by SPS. K-decreasing fatigue crack propagation tests were conducted using the DC(T) specimen (ASTM standard) with harmonic structure under the stress ratios, R, from 0.1 to 0.8 in ambient laboratory atmosphere. After testing, fracture surfaces were observed using scanning electron microscope (SEM), and crack profiles were analyzed using electron backscatter diffraction (EBSD) to discuss the mechanism of fatigue crack propagation. Threshold stress intensity range, ?Kth, of the material withharmonic structure decreased with stress ratio, R, whereas the effective stress intensity range, ?Keff, showedconstant value for R lower than 0.5. This result indicates that the influence of the stress ratio, R, on ?Kth of Ti-6Al-4V with harmonic structure can be concluded to be that on crack closure. Compared to the compactprepared from as-received powders with coarse acicular microstructure, ?Kth value of the material withharmonic structure was low. This was because the closure stress intensity, Kcl, in the material with harmonicstructure was lower than that of the coarse-grained material due to the existence of fine grains. In addition, theeffects of the grain size on the fatigue crack propagation behaviors of Ti-6Al-4V alloy were investigated for thebulk homogeneous material. The effects of the stress ratio and the grain size on the fatigue crack propagation of the material with harmonic structure were quantified.
Keywords: Ultra-fine grain